(NiZBRANNOE(B.s (Nt(B. IV /s - (NdEM^ENKO(B, (NwITALIJ gRIGORXEWI^(B.s; (NdEM^ENKO(B, (NwITALIJ gRIGORXEWI^s ((N~ERNOWCY (B:s [(NB(B. (NI(B.] ;s, 2011)
(Nw ^ETWERTIJ TOM WIBRANIH TWOR)QÆW WÆDOMOGO ^ERNÆWECXKOGO POETA wÆTALÆQ dEM^ENKA WWÆJ[LI POEZÆÇ Z POETI^NOGO ZBÆRNIKA (B"(NpOD WZGLQDOM gORGONY(B" (2010), "(NnA ZWEZDNOM WETRU(B" (NI (B"(NpREODOLENIE BOQZNI BEZDNY(B"(2011). (NwÆR[Æ NAPISANÆ ROSÆJSXKO@ MOWO@(B. (NwRAVA@TX SWOÇM LÆRIZMOM(B, (NNEBAJDUVÆST@ DO NAWKOLI[NXOGO VITTQ(B, (NSWOÇM BA^ENNQM OTO^U@^OGO(B. (NbUDE CÆKAWO@ WSÆM(B, (NHTO CÆKAWITXSQ TWOR^ÆST@ POETA(B.s)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (Nl)QÆTERATURA uKRAÇNIs)E -- (NpOEZ)QÆQs)E -- (NrOS)QÆJSXKOMOWNA(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E